Development and Validation of a Precise RP- HPLC Method to Determine Gentiopicroside Content in Cultures of Gentiana kurroo Royle - Alphonse, Mariadoss; Chandrasekaran, Rajasekaran; Pillay, Michael; Fulzele, Devanand P; Ramamoorthy, Siva; Thiyagarajan, Kalaivani (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Gentipicroside (GPD) is a major bioactive seco-iridoid glycoside in the methanolic extracts of roots and rhizomes of Gentiana kurroo Royle. GPD has antiinflammatory, antidiabetic, analgesic, antinociceptive, antibacterial and free radical scavenging activities. Although this compound was analyzed by various methods in different Gentiana species previously, no valid method was documented describing the accuracy and precision for the detection and quantification of GPD from in vitro samples of G. kurroo. Materials and Methods: A simple, accurate and highly sensitive reversed-phase high-performance liquid chromatographic (RP-HPLC) method was developed and validated according to the International Conference on Harmonization (ICH) guidelines. Results: Methanol and 0.1% acetic acid in millipore water [30:70, (v/v)] was used as a mobile phase and eluted at an isocratic flow rate of 1.0 ml/min under room temperature. The calibration curve was linear in the concentration range of 10-100 μg/ml with a correlation coefficient of 0.9967. The relative standard deviation (RSD) of repeatability and inter-day precision was less than 2%. The limit of detection (LOD) and limit of quantification (LOQ) of GPD was 0.083 μg/ml and 0.25 μg/ml, respectively. Recoveries from in vitro samples ranged from 91.0 to 114.0% and the precision of the method in terms of retention time (%RSD ≤ 2.01) and peak area (% RSD ≤5.11) were satisfactory. Conclusion: The validated RP-HPLC- PDA method can be used routinely for the determination of GPD in in vitro cultures and in vivo plants of G. kurroo.
Keywords: Gentiopicroside; RP-HPLC method development; Validation; In vitro cultures; Gentiana kurroo